Pengaruh Customer Experience Dan Kepuasan Terhadap Keputusan Pembelian Ulang Di Foodbox Kota Bima - Miftahul Janah; Intisari Haryanti; Sri Ernawati (Journal of Management and Social Sciences, 2023)
This type of research is associative research which aims to determine the effect of Customer Experience and Satisfaction on Repurchasing Decisions at Foodbox Kota Bima. The population in this study were all people in Kota Bima who had bought from Foodbox Kota Bima. The sample was determined by accidental sampling technique with 70 respondents. The data collection method used was observation, questionnaire (questionnaire), and library research. Data analysis techniques used in this study were instrument tests (validity and reliability tests), multiple linear regression analysis, correlation coefficients, coefficients of determination, T-tests, and F-tests, using the SPSS program. The results of the analysis using the t test show that the independent variable, namely Customer Experience (X1), has no significant effect on the repurchase decision (Y), and satisfaction (X2) has a positive and significant effect on the dependent variable, namely the repurchase decision (Y). Then the results of the analysis using the F test show that the two independent variables, namely Customer Experience (X1) and Satisfaction (X2), simultaneously have a significant effect on the dependent variable, namely Repeat Buyer Decision (Y).